Acute pancreatitis and refractory hypercalcemia in the third trimester caused by parathyroid carcinoma - Qingwen Nie; Shunlin Ouyang; Fang He (BMC, 2024)
Abstract Background Hypercalcemia can be a rare contributor to acute pancreatitis (AP) in pregnancy. This is primarily due to primary hyperparathyroidism (PHPT), resulting from parathyroid carcinoma. We exhibited a case report to analyze the diagnosis and treatment during the onset of hypercalcemia-induced AP. Case presentation A 32-year-old primigravida presented with acute pancreatitis near full-term gestation. Following a cesarean delivery, there was a reduction in serum amylase and peripancreatic exudate, but her serum calcium concentrations persistently elevated over 4.0 mmol/L. Interventions to lower the hypercalcemia were only temporarily effective, until a high serum parathyroid hormone (PTH) concentration of 1404 pg/mL was detected. Ultrasound revealed a 31 mm × 24 mm hypoechoic oval nodule in the left lower lobe of the thyroid gland. She underwent a parathyroidectomy, resulting in a dramatic decrease in serum PTH level, from preoperative levels of 2051 pg/mL to 299 pg/mL just 20 minutes after removal. Similarly, her serum calcium declined from 3.82 mmol/L to 1.73 mmol/L within 24 hours postoperatively. The final histopathology suggested parathyroid carcinoma. Conclusion When refractory hypercalcemia is present, serum PTH levels should be measured to determine PHPT. Parathyroidectomy is the optimal strategy for alleviating hypercalcemia and clarifying the underlying pathology.